The President: A Novel - Lewis, Alfred Henry, 1857-1914 (Salt Lake City, UT : Project Gutenberg, 2006)
"The President: A Novel" by Alfred Henry Lewis is a political fiction written in the early 20th century. It explores themes of ambition and power through its main character, Richard Storms, who is entangled in the world of Washington politics and captivated by the beautiful Dorothy Harley. His complex relationships with other characters, including the ambitious Senator Patrick Henry Hanway and the imposing Count Storri, set the stage for a narrative steeped in intrigue and romantic tension. The opening of the novel introduces Richard Storms in his luxurious Washington residence, where he is portrayed as a self-absorbed man seeking a purpose in life. His mundane morning routine contrasts sharply with the arrival of his breakfast and his thoughts of the beautiful Dorothy, whom he saved from an accident in the past. A romantic fascination with her is evident as he cherishes a memento of their encounter, a broken heel from her shoe. Meanwhile, the backdrop of socio-political maneuvering in Washington, as exemplified by the calculating Senator Hanway and the brutish Count Storri, hints at forthcoming conflict as Richard attempts to navigate both his romantic pursuits and the treacherous waters of political ambition. The stage is set for a tale of love, rivalry, and the complexities of power dynamics. (This is an automatically generated summary.)
Release date is 2006-06-13
E-text prepared by Suzanne Shell, Mary Meehan, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Fiction